Millimetre-Wave Cuboid Solid Immersion Lens with Intensity-Enhanced Amplitude Mask Apodization; Journal of Infrared, Millimeter, and Terahertz Waves; Vol. 39, iss. 6 - Yue Liyang; Bing Yan; Monks J. N. James; Dhama R. Rakesh; Zengbo Wang; Minin O. V. Oleg Vladilenovich; Minin I. V. Igor Vladilenovich (2018, 2018)
Title screen